YouTube Content as an Object of Fiduciary Collateral: A Maqashid Syariah Perspective - Amrih Makarimal Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
YouTube content has evolved into a valuable economic asset and can be used as an object of fiduciary collateral based on Government Regulation No. 24 of 2022 on the Creative Economy. This regulation recognizes intellectual property rights (IPR), including copyright over digital content, as a form of collateral that can be utilized to obtain financing from financial institutions. However, the implementation of YouTube content as fiduciary collateral still faces various challenges, particularly in legal, economic, and Maqashid Syariah compliance aspects. This study analyzes the ratio legis and ontological foundation of this policy and its implications from the perspective of Maqashid Syariah. Under Indonesia’s positive law, YouTube content as copyright is classified as an intangible asset recognized under Article 499 of the Indonesian Civil Code (KUH Perdata) and can be transferred through a fiduciary agreement. However, for it to be used as collateral, the content must have a clear economic value, be tradable, and provide legal certainty for creditors regarding collateral execution. From the Maqashid Syariah perspective, the principle of asset protection (hifzhul maal) plays a central role in determining the eligibility of an asset as collateral. YouTube content with stable economic value and clear ownership may align with this principle, as long as transactions do not involve gharar (uncertainty) and do not disadvantage any party. The research findings indicate that while YouTube content can legally serve as fiduciary collateral under Indonesia’s positive law, uncertainties remain in its implementation and enforcement. From the Maqashid Syariah perspective, ensuring legal certainty and transparency in transactions is crucial for this mechanism to align with Islamic principles of justice. Therefore, further regulatory measures are needed to ensure that digital content used as collateral meets the requirements of economic value certainty, lawful ownership, and a well-defined execution mechanism.